Chronic valproic acid intoxication in epileptology: diagnosis and treatment - N. A. Shnaider (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2016)
Valproic acid (VA) is used in epileptology for the basic and additional control of simple and complex focal seizures, absences, generalized tonicclonic seizures, and myoclonus. Information has been recently stored on cases of chronic overdosage of VA due to its blood accumulation. These conditions are described in the use of both high and average therapeutic doses of VA preparations in patients with a genetically determined delay in metabolism. The paper presents current methods for clinical and laboratory diagnosis and correction of chronic intoxication when valproic acid preparations are administered during the prehospital, hospital and rehabilitation phases of treatment. The authors note that a personalized approach is of importance for dose adjustment and prediction of unwanted adverse drug reactions associated with the use of VA preparations.